Risk and regulation of Islamic banking - Lewis, Mervyn; Mohamed Ariff, 1940-; Shamsher Mohamad (Cheltenham, UK ; Edward Elgar, 2014)
From a single product offering in 1963, the Islamic financial services industry has grown to an estimated $1.6 trillion in assets. Products must comply with profit and risk-sharing criteria and regulations preventing banks from venturing into activities with high risk and excessive uncertainty. This timely volume analyses these matters and considers the range of new products, discussing both conceptual and practical dimensions.
Includes bibliographical references and index.
Keywords: Banks and banking -- Religious aspects -- Islam